Pengaruh Promosi, Sistem Penambahan Modal, Dan Kualitas Pelayanan Terhadap Keputusan Pembiayaan Di PT Permodalan Nasional Madani Mekaar Unit Margasari 2 Kabupaten Tegal - Umi Mutmainah, Umi Mutmainah; Indah Dewi Mulyani; Nur Afridah; Andi Yulianto; Dumadi, Dumadi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study seeks to examine the extent to which promotion, the capital addition system, and service quality influence financing decisions at PT Permodalan Nasional Madani (PNM) Mekaar Unit Margasari 2, Tegal Regency. The research adopts a quantitative approach, relying on structured data collection methods through surveys distributed in the form of questionnaires. The respondents were selected from the official customer database of PT PNM Mekaar Unit Margasari 2, ensuring that the sample represented individuals directly involved with the company’s financing services. A total of 109 customers were chosen as the sample to reflect the broader population and to obtain results that are statistically reliable. The findings indicate that promotion, capital addition systems, and service quality each play a crucial role in shaping customers’ financing decisions. When analyzed simultaneously, these three variables demonstrate a significant and measurable effect, suggesting that improvements in promotional strategies, the design of capital addition mechanisms, and the overall quality of service delivery can directly increase customers’ willingness to engage in financing. These results highlight the importance of integrated management strategies within PT PNM Mekaar, emphasizing the need to continuously refine marketing efforts, optimize financial procedures, and maintain high service standards in order to build stronger customer trust and enhance decision-making outcomes.